Arabidopsis Novel Microgametophyte Defective Mutant 1 Is Required for Pollen Viability via Influencing Intine Development in Arabidopsis - Mi, Limin; Mo, Aowei; Yang, Jiange; Liu, Hui; Ren, Ding; Chen, Wanli; Long, Haifei; Jiang, Ning; Zhang, Tian; Lu, Pingli (Frontiers in Plant Science, 2022)
The pollen intine layer is necessary for male fertility in flowering plants. However, the mechanisms behind the developmental regulation of intine formation still remain largely unknown. Here, we identified a positive regulator, Arabidopsis novel microgametophyte defective mutant 1 (AtNMDM1), which influences male fertility by regulating intine formation. The AtNMDM1, encoding a pollen nuclei-localized protein, was highly expressed in the pollens at the late anther stages, 10–12. Both the mutations and the knock-down of AtNMDM1 resulted in pollen defects and significantly lowered the seed-setting rates. Genetic transmission analysis indicated that AtNMDM1 is a microgametophyte lethal gene. Calcofluor white staining revealed that abnormal cellulose distribution was present in the aborted pollen. Ultrastructural analyses showed that the abnormal intine rather than the exine led to pollen abortion. We further found, using transcriptome analysis, that cell wall modification was the most highly enriched gene ontology (GO) term used in the category of biological processes. Notably, two categories of genes, Arabinogalactan proteins (AGPs) and pectin methylesterases (PMEs) were greatly reduced, which were associated with pollen intine formation. In addition, we also identified another regulator, AtNMDM2, which interacted with AtNMDM1 in the pollen nuclei. Taken together, we identified a novel regulator, AtNMDM1 that affected cellulose distribution in the intine by regulating intine-related gene expression; furthermore, these results provide insights into the molecular mechanisms of pollen intine development.